The brain’s best friend: microglial neurotoxicity revisited - Hellwig, Sabine; Heinrich, Annette; Biber, Knut (Frontiers in Cellular Neuroscience, 2013)
One long standing aspect of microglia biology was never questioned; their involvement in brain disease. Based on morphological changes (retracted processes and amoeboid shape) that inevitably occur in these cells in case of damage in the CNS, microglia in the diseased brain were called “activated”. Because “activated” microglia were always found in direct neighborhood to dead or dying neuron, and since it is know now for more than 20 years that cultured microglia release numerous factors that are able to kill neurons, microglia “activation” was often seen as a neurotoxic process. From an evolutionary point of view, however, it is difficult to understand why an important, mostly post-mitotic and highly vulnerable organ like the brain would host numerous potential killers. This review is aimed to critically reconsider the term microglia neurotoxicity and to discuss experimental problems around microglia biology, that often have led to the conclusion that microglia are neurotoxic cells.